Kerja Dakwah dan Kerja Ilmiah-Positivistik dalam Konteks Pendidikan Tinggi Keagamaan Islam: Titik-Jumpa dan Titik-Pisah - Media Zainul Bahri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This article elucidates two main points. First, the difference between da’wah (Islamic preaching) activities and scientific-positivistic works. Da’wah, for example, is a theological work. To preach is to Invite/to call people to strengthen their beliefs and faith, do good, avoid bad deeds, and in many cases, preaching is to make judgments: right and wrong, misguidance or faith. Conversely, positivistic-scientific work is a scientific activity with methodological tools: there is empirical data (primary and secondary), there are approaches and theories, there are logical and rational explanations, and instead to strengthen belief and faith, scientific work is to find “scientific truth”. There are ontological, epistemological and objective differences between da’wah activities and scientific-positivistic ways. Second, to this day there is still a big problem related to Indonesian State Islamic University or Indonesian State Islamic Institute (UIN/IAIN): is this institution is a da’wah institution because there is an “Islam” within, or a scientific educational institution one because it is also a university that demands a scientific-positivistic ways. This article uses historical, theological and philosophical approaches.